2016
DOI: 10.1136/bmjqs-2016-005438
|View full text |Cite
|
Sign up to set email alerts
|

Six ways not to improve patient flow: a qualitative study

Abstract: Background Although well-established principles exist for improving the timeliness and efficiency of care, many organisations struggle to achieve more than small-scale, localised gains. Where care processes are complex and include segments under different groups' control, the elegant solutions promised by improvement methodologies remain elusive. This study sought to identify common design flaws that limit the impact of flow initiatives. Methods This qualitative study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 25 publications
(24 reference statements)
2
53
0
Order By: Relevance
“…The study’s quantitative component, which confirmed the lack of regional flow improvement and the negligible impact of most interventions, is reported as a supplement to the companion article [10]. This paper focuses on the study’s qualitative component; in-depth individual and small-group interviews (early 2013) with a purposive sample of 62 senior, middle and departmental managers constituted the primary method, supplemented by review of all available documents describing the nature, implementation, and/or impacts of flow initiatives.…”
Section: Methodsmentioning
confidence: 96%
“…The study’s quantitative component, which confirmed the lack of regional flow improvement and the negligible impact of most interventions, is reported as a supplement to the companion article [10]. This paper focuses on the study’s qualitative component; in-depth individual and small-group interviews (early 2013) with a purposive sample of 62 senior, middle and departmental managers constituted the primary method, supplemented by review of all available documents describing the nature, implementation, and/or impacts of flow initiatives.…”
Section: Methodsmentioning
confidence: 96%
“…Minor treatment areas were established in 4 EDs by 2008; as of early 2013, the other 2 sites nominally possessed them but were not using them. Nor did full implementation guarantee substantial impact on flow: some initiatives tackled too small a part of the problem to yield large effects; some demonstrated no effects at all …”
Section: Resultsmentioning
confidence: 99%
“…The overall case study's mixed‐methods design incorporated quantitative analysis of flow indicators 1999 to 2012; in‐depth interviews with 62 senior, middle, and departmental managers; review of ~700 documents solicited from managers throughout the organization; and participant observation of regional flow meetings/events in 2007 to 2009 and 2012 to 2014 . The present extension draws to a small extent on the interviews (the methods of which have been described in detail in the 2 prior articles) and observation, but most heavily on documentary sources.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations